Modeling, Evaluation, and Zoning of Marivan county Ecotourism Potential using Fuzzy Logic, FAHP, and TOPSIS - Balist, Jahanbakhsh; Heydarzadeh, Hamideh; Salehi, Esmail (Geographica Pannonica, 2019)
Among all the diverse regions of Iran, Marivan is considered one of the touring poles in the country thanks to its unique views which play an important role in providing ecotourism potential. Currently, despite the importance of the issue, no specific study and planning have been done to locate proper zones for an outing. In this regard, evaluation of the land potential for any kind of activity such as recreational planning is the first step in planning. In this study, we evaluated and zoned the ecotourism potential of Marivan in Kurdistan province with fuzzy logic, FAHP, and TOPSIS, based on 15 criteria and applying GIS, where the outcome was zoning map of areas most suitable for ecotourism development. The results indicated that a total area of 3183 km2 (included in the study), classes 4 and 5, respectively, with 151 and 513 km2 constitute the most appropriate zones for ecotourism development. Among points with ecotourism attraction, the Zarivar Lake claimed the top priority while Anjiran Heights received the last priority.